The impact of social media at work on job performance among government employees : perspective from the stress-strain-outcome and social capital theory - Nur Muneerah, Kasim (2023)
The pervasiveness of social media (SM) use in organizations is a relevant driver that can influence an employee's job performance. Several researchers have considered the direct role of social media usage in influencing job performance. However, limited studies explore how social media use may impact employees' job performance, especially innovativeness. Moreover, inconsistencies exist in the literature regarding whether social media improves or reduce employees' job performance. By integrating the Stressor Strain Outcome (SSO) model and Social Capital Theory, this study aimed to explore how SM use influences public sector employees' innovative job performance in the Malaysian context. Besides, integrating both theories will discover the advantages and disadvantages of social media, extending the comprehension of their value for work purposes. The significance of this study explains several outputs that can benefit employees, management, and the government. Hence, fourteen hypotheses are outlined to support the study's objectives, focusing on the association between SM use and job performance among public sector employees. In the methodology part, this study applies positivism as a research paradigm, and the study was conducted based on a quantitative approach. Meanwhile, the instrument of this study is a questionnaire, and items were adapted from previously validated studies. The data was collected through an online survey, and 317 employees from the public sector participated. The partial least square structural equation modelling (PLS-SEM) technique was applied in data analysis for this study's measurement model and structural model assessment. The findings discovered that social media use at work has a mild but statistically significant influence on information overload, communication overload, and social overload. In addition, information overload and communication overload positively influence technostress. However, SM use at work has not significantly influenced social overload, and technostress does not impact innovative job performance. The following finding shows that SM use predicts network ties, shared vision, and trust significantly. Besides, network ties and trust positively promoted work engagement except for shared vision. Subsequently, work engagement was associated with innovative job performance. Reflecting on the lack of empirical research on SM use related to innovative performance in a workplace setting, this study extends the existing literature on the advantage and disadvantages of SM use at work by integrating both theories, the SSO model and SCT. Hence, these theories enrich the understanding of the employee's strengths, weaknesses, opportunities, and threats due to SM use in the workplace. In addition, this study provides valuable insight into the following parties related to the organizational stakeholders, including employees themselves, employers, and the government concerning SM use at work. Employers and governments can offer mitigating plans and efforts on the issues of SM use at work concerning employees' innovative performance, including revising or strengthening the policy or rules. Therefore, the study has theoretically and practically contributed to the field by integrating different perspectives on SM use at work towards employee innovative performance.